Influence of African Traditional Religion and spirituality in understanding chronic illnesses and its implications for social work practice:a case of Chiweshe Communal lands in Zimbabwe - Mabvurira, Vincent (University of Limpopo, 2016)
Refer to document
Thesis (Ph. D. (Social Work)) -- University of Limpopo, 2016
Keywords: African Traditional Religion; Spirituality; Chronic illnesses; Social work practice; Religions -- African influences; Social workers -- Zimbabwe; Spirituality -- Zimbabwe; Chronic diseases